PERAN HUBUNGAN MASYARAKAT DALAM MENINGKATKAN CITRA PERUSAHAAN MELALUI PELAKSANAAN PROGRAM TANGGUNG JAWAB SOSIAL PERUSAHAAN - Moh. Badrus Solichin (Istithmar: Jurnal Studi Ekonomi Syariah, 2019)
Public relation is a communication activity that aims to build good image of company. Furthermore public relation is a planning that uses persuasive communication to influence society perception and a planning to influence society perception through the implementation of social responsibility program based on interrelationship communication to achieve the goodness between each other. As communication instrument with public, company social responsibility to society or well known as corporate social responsibility (CSR) is used to share positive effect of company for local society environment, environmental conservation activity and the result to the public. Respond and view to the company responsibility from several parts, costumer and society are used to be feedback to change company approach in managing environment and to improve company image that will influence on company profit improvement.